Mapping evidence on factors contributing to maternal and child mortality in sub-Saharan Africa: A scoping review protocol. - Ugochinyere I Nwagbara; Emmanuella C Osuala; Rumbidzai Chireshe; Gbotemi B Babatunde; Ngozichika O Okeke; Nnennaya Opara; Khumbulani W Hlongwana (PLoS ONE)
Background Maternal and child mortality remains a major public health issue in sub-Saharan Africa (SSA), with the region having the highest under-five mortality rates, where approximately 1 in 11 children, dies before the age of 5 years. This is nearly 15 times the average in high-income countries (HICs). This scoping review is aimed at mapping evidence on the factors contributing to maternal and child mortality in SSA. Methods This study will be conducted using a scoping review to map existing literature on the factors contributing to maternal and child mortality in SSA. The search will comprise of peer-reviewed and grey literature, using the EBSCOhost platform. Keyword search from electronic databases such as PubMed/MEDLINE, Google Scholar, Science Direct and World Health Organization library, will be conducted. Information will be obtained from the included studies, using a data charting table. We will use NVIVO version 10 software to analyse the data, and the narrative account of the study will be presented by means of a thematic content analysis. Discussion We expect to find relevant literature that can help us in mapping evidence on the factors contributing to maternal and child mortality in SSA. This study results are anticipated to identify research gaps and in turn, guide the design of future primary studies. Systematic review protocol registration Open Science Framework registration number (DOI 10.17605/OSF.IO/XF5VN).